Desenvolvimento de uma proposta de indicadores para avaliação do desempenho ambiental dos processos produtivos industriais sob a ótica da biomimética - Sette, Tânia Cristina Campanhol (Universidade do Vale do Rio dos Sinos, 2010)
This work presents the development of a proposal of indicators for assessing the environmental performance of industrial processes, taking as parameters the ten Principles of Mature Natural Systems, described by Biomimetics: (1) use waste as a resource, (2) diversifying, cooperate to the full use of habitat, (3) assimilate and use energy efficiently, (4) enhance rather than exploit to the maximum (5) use materials sparingly, (6) does not mess your address, (7) do not deplete resources, (8) remain in equilibrium with the biosphere, (9) operate on the basis of information (10) consume resources of their own habitat. The Biomimicry studies models of nature and then imitates or draws them to understand and propose solutions to human problems. So for this new approach, manufacturing processes of industries should incorporate principles which are used by animals and plants, for example, use sunlight and simple compounds to produce fibers, plastics and chemicals completely biodegradable. Parallel studies on the concepts of methods of environmental management in industry: Eco-Efficiency, Cleaner Production, ISO, Industrial Ecology and Zeri Methodology. The methods of industrial environmental performance assessment, models for building systems of indicators and analysis of environmental assessment indicators were subsequently raised developed by different parties to the industrial sector. For each Principle is suggested one indicator, except for the 3 and 4 Principles, which identified the importance of using a pressure gauge and another response, considering the current lack of structural changes in global energy production and use of materials. This led to determination of twelve indicators that represent the behavior of industrial aspects aligned to the Principles of Natural Systems. It is analyze the performance of industrial aspects activity from the viewpoint of an efficiency standard that includes a differentiated strategy contained in the Principles of Natural Systems Mature, base of this work. Certainly this concept can contribute effectively to the development of environmental sustainability from the industrial activity.
Keywords: Biomimética; Indicadores ambientais industriais; Sistemas de avaliação ambiental; Biomimicry; Industrial environmental indicators; Systems environmental assessment; ACCNPQ::Engenharias::Engenharia de Produção